The Implications of Land Use Dynamics on Land Disputes in Depok City, West Java - Whidayanti, Ella (Pusat Penelitian dan Pengabdian kepada Masyarakat, Sekolah Tinggi Pertanahan Nasional, 2025)
Abstract: Land use dynamics represent an inevitable phenomenon in the process of urban development. The large-scale conversion of land in Depok City, West Java, has triggered various issues, particularly concerning land tenure, land use practices, and the emergence of land disputes—especially on particuliere lands, whose legal status remains ambiguous due to historical and administrative complexities. This phenomenon has significant implications for spatial and environmental sustainability and also exacerbates social tensions and conflicts related to land ownership. This study seeks to analyze the correlation between land use transformation and the rising frequency of land disputes in Depok City, while also identifying effective and equitable mechanisms for conflict resolution. This study employs a qualitative case study approach that integrates secondary data analysis and in-depth interviews to understand the dynamics of land tenure conflicts. The primary issue identified lies in the structural imbalance between escalating land demand and the limited supply of available land parcels within the urban landscape. Land disputes may be addressed through two primary pathways: litigation processes within judicial institutions and alternative non-litigation mechanisms that emphasize cooperative approaches outside formal legal proceedings. With the increasing complexity of land-related conflicts, alternative dispute resolution mechanisms—such as consultation, negotiation, mediation, conciliation, and expert evaluation—have become increasingly pertinent and contextually appropriate. The findings of this study indicate that land disputes in Depok City are driven by land imbalance and weak governance, with non-litigation settlements offering a more efficient and equitable approach that serves as the basis for adaptive land policy recommendations. Keywords: Land Use Dynamics, Land Disputes, Depok City.